Sport-specific training induced adaptations in postural control and their relationship with athletic performance - Zemková, Erika; Kováčiková, Zuzana (Frontiers in Human Neuroscience, 2023)
The effects of various exercise programs on postural balance control in athletes and their underlying physiological mechanisms have been extensively investigated. However, a little is known how challenging sport-specific conditions contribute to the improvement of static or dynamic balance and to what extent it may be explained by adaptations in sensorimotor and/or neuromuscular functions. The analysis of the literature could provide useful information on interpretation of changes in postural sway variables in response to long-term sport-specific training and their associations with performance measures. Therefore, this scoping review aims (i) to map the literature that addresses the relationship of postural balance control to athletic performance as a result of neurophysiological adaptations induced by sport-specific balance exercises, and (ii) to identify gaps in the existing literature and propose future research on this topic. The main literature search conducted on MEDLINE, Web of Science, Scopus, PubMed and Cochrane Library databases was completed by SpringerLink, Elsevier and Google Scholar. A total of 126 articles met the inclusion criteria. However, the association between variables of postural balance control and measures of sport-specific performance was investigated only in 14 articles. A relationship between static or dynamic balance and criterion measures of athletic performance was revealed in shooting, archery, golf, baseball, ice-hockey, tennis, and snowboarding. This may be ascribed to improved ability of athletes to perform postural adjustments in highly balance task demands. However, the extent to which sport-specific exercises contribute to their better balance is unknown. Although there is a good deal of evidence supporting neurophysiological adaptations in postural balance control induced by body conditioning exercises, a little effort has been made to explain balance adaptations induced by sport-specific exercises and their effects on athletic performance. While an enhancement in the athletic performance is often attributed to an improvement of neuromuscular functions induced by sport-specific balance exercises, it can be equally well ascribed to their improvement by general body conditioning exercises. Therefore, the relevant experiments have yet to be conducted to investigate the relative contributions of each of these exercises to improving athletic performance.